Research for association and correlation between stress at workplace and individual mental health - Lee, Mi-Jeong; Lee, Wanhyung (Frontiers in Public Health, 2024)
BackgroundOccupational stress negatively affects mental health and productivity. Managing worker mental health has been equated to assessing workplace stressors, although there are challenges in screening and managing the mental health of vulnerable workers. This study aimed to determine the correlation between workplace stress characteristics and two depression assessment questionnaires to guide workplaces on assessing job stress more effectively.MethodsA cross-sectional survey study was conducted with 812 workers from manufacturing sector in Korea. Depression was measured using the CES-D and PHQ-9 questionnaires, and the KOSS-SF was used to assess job stress.ResultsThe results showed that 26.2% of participants had high job stress levels, with job control and demands being the highest subfactors. The CES-D and PHQ-9 were positively correlated with job stress factors, with the PHQ-9 showing stronger correlations than the CES-D.ConclusionThe CES-D and PHQ-9 were associated with workplace stress; however, the CES-D was not associated with job control, whereas the PHQ-9 was not associated with job demands or relationship conflicts. Additionally, the PHQ-9 showed a higher correlation with workplace stress than the CES-D. The correlation between depression screening tests differed according to workplace stress characteristics, but the PHQ-9 was helpful in screening workers for depression.